Outbreak of Acute Respiratory Illness Associated With Human Adenovirus Type 4 at the United States Coast Guard Academy, 2019. (17th June 2021) - Chu, Victoria T; Simon, Esan; Lu, Xiaoyan; Rockwell, Patrick; Abedi, Glen R; Gardner, Christopher; Kujawski, Stephanie A; Schneider, Eileen; Gentile, Micah; Ramsey, Lee Ann; Liu, Robert; Jones, Sydney; et al.
Abstract: Background: Although a human adenovirus (HAdV) vaccine is available for military use, officers-in-training are not routinely vaccinated. We describe an HAdV-associated respiratory outbreak among unvaccinated cadets at the US Coast Guard Academy and its impact on cadet training. Methods: We defined a case as a cadet with new onset cough or sore throat during August 1–October 4, 2019. We reviewed medical records and distributed a questionnaire to identify cases and to estimate impact on cadet training. We performed real-time polymerase chain reaction testing on patient and environmental samples and whole genome sequencing on a subset of positive patient samples. Results: Among the 1072 cadets, 378 (35%) cases were identified by medical records (n = 230) or additionally by the questionnaire (n = 148). Of the 230 cases identified from medical records, 138 (60%) were male and 226 (98%) had no underlying conditions. From questionnaire responses, 113 of 228 (50%) cases reported duty restrictions. Of cases with respiratory specimens, 36 of 50 (72%) were HAdV positive; all 14 sequenced specimens were HAdV-4a1. Sixteen (89%) of 18 environmental specimens from the cadet dormitory were HAdV-positive. Conclusions: The HAdV-4-associated outbreak infected a substantial number of cadets and significantly impacted cadet training. Routine vaccination could prevent HAdV respiratory outbreaks in this population. Abstract : We describe a human adenovirus (HAdV)-associated respiratory outbreak affecting one third of the unvaccinated cadet population and significantly impacting mandatory training. Establishing an HAdV vaccination program in this military population could prevent future HADV-associated respiratory outbreaks.